Older workers as a source of wisdom capital: broadening perspectives (REGE Revista de Gestão, 2018)
AbstractPurpose – The purpose of this paper is to pinpoint some key variables that help shape the notion of olderworkers as a source of organizational wisdom capital. Design/methodology/approach – Toward that end, the paper reviews a selective bibliography in order tosupport its arguments. Findings – The evidence garnered throughout this paper – fundamentally through different lens ofanalysis – suggests that older workers may be considered as valuable assets. Furthermore, a sizeablenumber of members of this cohort continue, even in the latter stages of their careers, to be willing,well-equipped, and able to enhance, if properly utilized, companies to achieve other patterns ofperformance. Accordingly, it is advocated here that their knowledge and expertise constitutes an authenticsource of organizational wisdom capital that deserves careful attention from organizations to maintain bymeans of suitable incentives and training. Research limitations/implications – This paper highlights other aspects that should not be disdained byorganizations such as career-ending, work characteristics, and mastery-avoidance goals. Thus, companiesthat are interested in keeping older talents must be attuned to their wishes and aspirations, as well as beingproactive by offering tailor-made job-products to them. Social implications – Given the trend of aging workforce, it is likely that organizations will be increasinglyimpacted by societal demands and public policies toward benefiting and respecting older talents. Originality/value – This paper advocates that older workers are usually living memories of organizationallife. Rather, they tend to keep in their minds those failures and successful ideas, projects, initiatives,and leaderships, which added or not value throughout their trajectories, as well as things that worked out or not.Fundamentally, they are able to provide answers to vital questions. Keywords Creativity, Older workers, Engagement, Motivation, Emotion regulation, Job performance